ISSUES OF LOGISTICS DEVELOPMENT IN THE FIELD OF TOURISM (British Journal of Global Ecology and Sustainable Development, 2024)
This article examines the role and importance of logistics in tourism. Transport logistics is one of the important components in the field of tourism. The direction of logistics in tourism is the main service in the field of tourism and is inextricably linked with the provision of services to tourists in travel, excursions and tours, vehicles, tourist routes, and organizations providing transport services.